Study of some climate indicators at the Institute of Animal Science from 1967 to 2013 and their relation with grasses - Herrera, R.; García, M.; Cruz, Ana M. (Cuban Journal of Agricultural Science, 2018)
The performance of some climate indicators (total rainfall, number of days with rain, minimum, maximum and mean temperatures, minimum temperature less than 15 °C and maximum temperature higher than 27 °C) was studied during the period 1967-2013. The statistics mean or total value (according to the indicator) per year and climatic season (rainy and dry season), standard deviation, variance and coefficient of variation were determined, and linear regression equation was fitted between climatic indicators and decades. The number of days with rain decreased from 93.7 in the decade 1970-1979 to 81.1 in the period 2000-2009, with standard deviation, variance and coefficient of variation of 5.73, 32.78 and 9.59 %, respectively as well as r = -0.97 (P < 0.0001). Total rainfall decreased from 1,459.6 mm in the decade 1970-1979 up to 1,327.6 mm in the 2000-2009 stage, with standard deviation, variance and coefficient of variation of 30.49, 929.42 and 2.79 %, respectively as well as r = -0.87 (P <0.0001 ). The number of days with maximum temperature higher than 27 °C increased from 222.9 in the decade 1970-1979 up to 279.6 in the period 2000-2009, with standard deviation, variance and coefficient of variation of 15.25, 232.70 and 10.32 %, respectively as well as r=0.99 (P <0.0001). The number of days with minimum temperature less than 15 °C decreased from 57.4 in the decade 1970-1979 up to 43.9 in the period 2000-2009, with standard deviation, variance and coefficient of variation of 7.33, 53.72 and 14.59%, respectively as well as r=-0.92 (P <0.0001). The maximum temperature increased from 29.6 °C in the decade 1970-1979 up to 30.8 °C in the period 2000-2009, with standard deviation, variance and coefficient of variation of 0.60, 0.06 and 1.88 %, respectively as well as r = 0.95 (P <0.0001) . The minimum temperature increased from 20.4 °C in the decade 1970-1979 to 23.4 °C in the period 2000-2009, with standard deviation, variance and coefficient of variation of 1.31, 1.71 and 6.09%, respectively as well as r = 0.95 (P <0.0001). Mean temperature increased from 23.8 °C in the decade 1970-1979 to 26.7 °C in the period 2000-2009, with standard deviation, variance and coefficient of variation of 0.66, 0.64 and 2.50 %, respectively as well as r = 0.92 (P <0.0001). During dry and rainy season, indicators had similar performance, but with specific values for each one of them. When applying these results in Cenchrus purpureus, there was a decrease in yield and an increase in height when comparing the decade 1979 versus 2010. The profile of indicators studied in 40 years (baseline) is available and compared with what happened in the period 2010 -2013. Variability of indicators by decade and climate season is known. The presence of climate change is appreciated. There are databases that allow to establish longer-term prediction models and their impact on forage biomass production. Key words: rain, temperature, seasonal values